Reviews in environmental health: How systematic are they? - Patrice Sutton; Nicholas Chartres; Swati D.G. Rayasam; Natalyn Daniels; Juleen Lam; Eman Maghrbi; Tracey J. Woodruff (Environment International, 2021)
Background: Synthesizing environmental health science is crucial to taking action to protect public health. Procedures for evidence evaluation and integration are transitioning from “expert-based narrative” to “systematic” review methods. However, little is known about the methodology being utilized for either type of review. Objectives: To appraise the methodological strengths and weaknesses of a sample of “expert-based narrative” and “systematic” reviews in environmental health. Methods: We conducted a comprehensive search of multiple databases and identified relevant reviews using pre-specified eligibility criteria. We applied a modified version of the Literature Review Appraisal Toolkit (LRAT) to three environmental health topics that assessed the utility, validity and transparency of reviews. Results: We identified 29 reviews published between 2003 and 2019, of which 13 (45%) were self-identified as systematic reviews. Across every LRAT domain, systematic reviews received a higher percentage of “satisfactory” ratings compared to non-systematic reviews. In eight of these domains, there was a statistically significant difference observed between the two types of reviews and “satisfactory” ratings. Non-systematic reviews performed poorly with the majority receiving an “unsatisfactory” or “unclear” rating in 11 of the 12 domains. Systematic reviews performed poorly in six of the 12 domains; 10 (77%) did not state the reviews objectives or develop a protocol; eight (62%) did not state the roles and contribution of the authors, or evaluate the internal validity of the included evidence consistently using a valid method; and only seven (54%) stated a pre-defined definition of the evidence bar on which their conclusions were based, or had an author disclosure of interest statement. Discussion: Systematic reviews produced more useful, valid, and transparent conclusions compared to non-systematic reviews, but poorly conducted systematic reviews were prevalent. Ongoing development and implementation of empirically based systematic review methods are required in environmental health to ensure transparent and timely decision making to protect the public’s health.